Optical solitons and other solutions to the conformable space-time fractional Fokas-Lenells equation - Bulut, Hasan; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet; Rezazadeh, Hadi; Eslami, Mostafa; Mirzazadeh, Mohammad (Elsevier Gmbh, 2018)
This study reveals the dark, bright, combined dark bright, singular optical solitons and other solutions to the conformable space time fractional Fokas-Lenells equation. We use two integral schemes in reaching such solutions. The constraints conditions which guarantee the existence of valid solutions are stated. By choosing the suitable values of the parameters involved, we plot the 2-dimensional and 3-dimensional surfaces to some of the obtained solutions.
Keywords: Fractional derivative; Fokas-Lenells equation; Solitons